The Impact of Trauma Simulation on Pre-Hospital Emergency Operations Staff - Mehri Bozorgnejad; Tahere Najafi; Shima Haghani; Peyman Nazari (نشریه پرستاری ایران, 2022)
Background & Aims: Trauma is the main cause of death and disability in the world. Pre-hospital care is the first line of trauma care and treatment. Pre-hospital emergency services include immediate actions to save lives. Simulation allows employees to acquire basic skills in thinking, evaluating, solving problems, making decisions and analyzing data. Materials & Methods: This is a quasi-experimental study with a pre-test/post-test design. The participants were 60 pre-hospital emergency staff selected from among 200 staff of Fars pre-hospital emergency center . The simulation training was based on an educational model. The clinical skills of the participants in dealing with trauma patients was evaluated by the Objective Structured Clinical Skills Evaluation method in nine areas. After the training, the skills were re-evaluated and analyzed in SPSS v. 22 software. Results: The lowest mean score (from 0 to 100) was related to the skill of using traction splint (71.01±18.73) and the highest score was related to the skill of bleeding control and shock treatment (81.04±22.75). The results of the paired t-test showed that the overall clinical skill and nine standard skills of dealing with trauma patients were significantly increased after simulation training (P<0.001). Conclusion: The simulation training can increase the skills of pre-hospital emergency staff in dealing with trauma patients.